Advancing service offerings in food and nutrition metrology: the updated METROFOOD-RI service chart - De Bruyn, C.; Sharma, S.; Zoani, C.; Van Loco, Joris (Frontiers in Nutrition, 2025)
METROFOOD-RI is a pan-European research infrastructure (RI) dedicated to promoting metrology in food and nutrition, integrating an array of interdisciplinary fields such as agrifood, food safety and quality, traceability, human health, and environmental sustainability. A core element of METROFOOD-RI's implementation is its service chart, including a structured catalog which provides an overview of the services offered across its network of facilities. During the Early Phase Implementation project (METROFOOD-EPI), the consortium undertook a comprehensive update of the service chart, addressing limitations from the Preparatory Phase (METROFOOD-PP) and aligning the service portfolio with current capabilities and user needs. This article presents the context and outcomes of the service chart update in a scientific framework. We describe the rationale for revising the original service chart, and the methodological steps followed to refine service categorization. The updated service chart is organized into four primary categories: Research services, ICT and Data services, Advisory services, and Education and Training services. Within these, the Research category is further structured into sub-domains (Agrifood, Metrology tools, Health, Environment & Sustainability) to encompass the RI's broad scope. We detail the definitions and rationale for each category and subcategory, highlighting how this structure integrates services across domains and aligns with key priorities in agrifood innovation, public health, sustainability, and metrology. The updated chart improves internal coordination among METROFOOD-RI partners by aligning resources to identified needs and revealing gaps, and also enhances external user experience by allowing easy navigation of available services through its associated catalog. Finally, we discuss the value of the service chart as a foundation for future tools, such as a METROFOOD-RI online access portal and a membership app, and its role in supporting a multidisciplinary, open science approach.